Competitive Productivity (CP) as an emergent phenomenon: Methods for modelling micro, meso, and macro levels. (August 2022) - Winzar, Hume; Baumann, Chris; Soboleva, Alena; Park, Seung Ho; Pitt, David
Abstract: This paper argues that hospitality enterprises are a part of a complex-adaptive system. The exploration of Competitive Productivity (CP) and related concepts at the macro, meso, and micro (M-M-M) levels requires that we understand interrelationships beyond traditional analytical tools. We propose three approaches to testing M-M-M CP architecture interactions: multi-level modeling, social network modeling, and agent-based modeling. Examples from the hospitality literature are offered for multi-level modeling and agent-based modeling, and we illustrate social networks by showing that IJHM authors network to create a highly competitive journal. Multi-level modeling is useful for top-down testing (macro → meso → micro), but unsuitable for bottom-up modeling (micro → meso → macro) without making unrealistic assumptions about the nature of data. Interactions at the micro-level produce meso-level and macro-level behaviors, emergent phenomena that cannot be inferred by examining micro-level agents or behaviors. Social network theory and agent-based modeling are viable alternatives for examining and modeling emergent phenomena. Highlights: Hospitality businesses constitute a complex adaptive system where entities affect entities within a dynamic environment Such entities must be considered at the appropriate units of analysis at Micro, Meso, Macro levels. Culture, profitability, Competitive Productivity are emergent properties of interactions within a complex adaptive system. Emergent phenomena cannot be seen from the properties of entities within the complex system. Understanding emergence requires analytical tools beyond our traditional frameworks. We suggest authors consider Multi-level models, Social networks, Agent-based models as analytical tools. We provide examples of each from the Hospitality literature and suggestions for when each tool is appropriate.